Bricks non-destructive simulation testing method utilizing neutron radiography facility based on a 7Li(p,n)7Be reaction - Jacob G. Fantidis; Athanasia Κ. Thomoglou; Maristella Ε. Voutetaki; Bassam Tayeh; George Nikolaou (Nuclear Engineering and Technology)
The evaluation of non-destructive neutron radiography (NR) for examining the internal composition of various structural materials, has been the focus of extensive research. This manuscript uses non-destructive testing to generate three-dimensional radiographs of three different brick structural materials: glass block, magnesia-chrome, and lead to evaluate their capability to withstand fast neutrons and gammas emitted from a source. When neutrons with thermal or epithermal spectrum are required, the optimum combination for an accelerator was simulated using a 2.8 MeV proton beam on a lithium target. The presented facility tested both thermal and fast neutron radiography. This study examined various aperture diameters and collimator lengths. It found that implementing a special fast neutron filter significantly increased the thermal neutron content (TNC) with minimal impact on the thermal neutron flux. For fast neutron radiography, the study evaluated parameters such as geometric unsharpness, fast neutron flux, and the percentage of the uncollided fast neutron reaching the object. Both neutrons and photons from the source were used to inspect faults in a glass brick.